KETERAMPILAN BERTANYA GURU KELAS IV SDN MANGKAUK 2 DI MASA PANDEMI COVID-19 - Johan Arifin; Rahidatul Laila Agustina (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
This study aims to describe how the ability of teachers to apply questioning skills to social studies subjects during the Covid-19 pandemic. This study uses a qualitative approach. The data sources used in this study were fourth grade teachers at SDN Mangkauk 2. The subjects of this study were the principal, fourth grade teachers, and fourth grade students. Data collection techniques used in this study were observation and interview techniques. The data analysis technique was carried out by collecting data/data collection, data condensation, data presentation/data display and drawing conclusions. The conclusion of this research is that the teacher's ability to apply questioning skills for fourth grade students at SDN Mangkauk 2 during the current covid-19 pandemic is not optimal, this is due to the limitations of the learning process, learning is carried out remotely not face to face and when learning takes place only some students who can interact and respond when the teacher is learning. Keywords: Questioning Skills, Covid-19 Pandemic